Bone loading and the spine: Total body and lumbar bone mineral density in elite male gymnasts, swimmers and controls - Gannon, L.; Hind, K (Journal of Clinical Densitometry, 2016)
Elite gymnastics and swimming demand long hours of training, involving contrasting magnitudes of forces on the skeleton. Although gravitational skeletal loading is associated with positive increases in total bone mineral density (BMD), little is known about the effect of such training on site-specific BMD in young athletic males at different ages across the development of peak bone mass. The purpose of the study was to explore the bone mineral properties of young male athletes involved in high impact (gymnastics) versus low impact (swimming) sports.